GLOBECOM 2009 - 2009 IEEE Global Telecommunications Conference 2009
DOI: 10.1109/glocom.2009.5425697
|View full text |Cite
|
Sign up to set email alerts
|

Low-Complexity Algorithm for Log Likelihood Ratios in Coded MIMO-OFDM Communications

Abstract: This paper proposes a low-complexity algorithm to calculate log likelihood ratios (LLRs) of coded bits, which is necessary for channel decoding in coded MIMO-OFDM mobile communications. An approximate LLR needs to find a pair of transmitted signal candidates that can maximize the log likelihood function under a constraint that a coded bit be equal to either one or zero. The proposed algorithm can find such a pair simultaneously, whereas conventional ones find them individually. Specifically, the proposed metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The detected signal is selected from hard decisions of both the MMSE detection result and the unquantized signal candidates on the basis of the log likelihood function. Computer simulations under a correlated Rayleigh flat fading channel have shown that the proposed scheme provides an excellent trade-off between BER performance and complexity, and that it outperforms conventional one-dimensional search algorithms, PM [5] and plural PM [7] while requiring much less complexity than the conventional algorithms. It was also shown that the proposed algorithm can reduce the complexity about 7.4% of that required by GD, 12.1% of that required by PM, and 5.4% of that required by plural PM, when the number of receive or transmit antennas is equal to 8, QPSK is used as the modulation scheme, and average E b /N 0 is equal to 30 dB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The detected signal is selected from hard decisions of both the MMSE detection result and the unquantized signal candidates on the basis of the log likelihood function. Computer simulations under a correlated Rayleigh flat fading channel have shown that the proposed scheme provides an excellent trade-off between BER performance and complexity, and that it outperforms conventional one-dimensional search algorithms, PM [5] and plural PM [7] while requiring much less complexity than the conventional algorithms. It was also shown that the proposed algorithm can reduce the complexity about 7.4% of that required by GD, 12.1% of that required by PM, and 5.4% of that required by plural PM, when the number of receive or transmit antennas is equal to 8, QPSK is used as the modulation scheme, and average E b /N 0 is equal to 30 dB.…”
Section: Discussionmentioning
confidence: 99%
“…Note that (52) coincides with the one-dimensional search in [5], which is referred to as the projection method (PM). PM can be extended into plural one-dimensional search, plural PM [7] aŝ…”
Section: Relation Between Proposed and Pm Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations